The Effect of Care Instruction to Family Caregivers of Children with Cerebral Palsy on Life Quality of Care Givers - Nikta Hatami-Zadeh; Mohammad Ali Hosseini; Mehdi Rahgozar; Manoochehr Arjmand; Mohammad Saeed Khanjani (University of Social Welfare and Rehabilitation Sciences, 2009)
Objective: Since presence of cerebral palsied child affects the life quality of family and specially family caregivers, the aim of this study was to determine the effect of education to caregivers about caring of children with cerebral palsy on quality of life of them. Materials & Methods: In this interventional and quasi-experimental study, twenty five family caregivers of spastic cerebral palsy children were selected based on inclusion criteria from welfare centers of Babolsar. Instruction courses performed 6-8 sessions and each session takes 30 minutes. The quality of life was assessed using SF36 (short form health survey with 36 question) at the beginning and 3 months after the instruction courses . Paired T test and Wilcoxon nonparametric test were used for data analysis. Results: The scores of quality of life followed by instruction courses showed that there was meaningful improvement in whole of eight realms , both total realms of physical health and mental health ,as well as total quality of life (P<0.001) .The minimum increase in mean difference found in mental health(11.36±13.59) and the maximum increase found in emotional role (50.66±87.24). The amount of change between pre test and post test in the score of total quality of life was (13.18±13.54). Conclusion: Findings of this study showed that life quality of family caregivers promoted after instruction about how to do correct care on cerebral palsied children. therefore, the importance of family instruction can be concluded for better life of cerebral palsied child caregivers. It should be noted that the effectiveness of rehabilitation program for cerebral palsied children might have positive effects on life quality of their caregivers.